2006
DOI: 10.1091/mbc.e05-04-0284
|View full text |Cite
|
Sign up to set email alerts
|

RhoA GTPase Regulates M-Cadherin Activity and Myoblast Fusion

Abstract: The Rho family of GTP-binding proteins plays critical roles during myogenesis induction. To elucidate their role later during myogenesis, we have analyzed RhoA function during myoblast fusion into myotubes. We find that RhoA activity is rapidly and transiently increased when cells are shifted into differentiation medium and then is decreased until myoblast fusion. RhoA activity must be down-regulated to allow fusion, because expression of a constitutively active form of RhoA (RhoAV14) inhibits this process. Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 48 publications
7
131
1
Order By: Relevance
“…Interestingly, we show that this particularly well-conserved region related to PKN and predicted to display a coiled-coil structure is necessary to bind RhoA, suggesting that the effect of Fam65b on myoblast fusion may depend on its ability to interact with RhoA and to inhibit its activity. Consistent with this model, other investigators showed that a decrease in RhoA-GTP content was indispensable to allow myoblast fusion (32). Therefore, we consider it very likely that Fam65b behaves as an inducible repressor of RhoA activity to allow cellcell fusion during muscle or placenta formation.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, we show that this particularly well-conserved region related to PKN and predicted to display a coiled-coil structure is necessary to bind RhoA, suggesting that the effect of Fam65b on myoblast fusion may depend on its ability to interact with RhoA and to inhibit its activity. Consistent with this model, other investigators showed that a decrease in RhoA-GTP content was indispensable to allow myoblast fusion (32). Therefore, we consider it very likely that Fam65b behaves as an inducible repressor of RhoA activity to allow cellcell fusion during muscle or placenta formation.…”
Section: Discussionsupporting
confidence: 86%
“…We demonstrate a transient but substantial and celldensity-dependent increase in RhoA activity 12-24 hours after initiation of differentiation -a period not investigated by Nishiyama et al (Nishiyama et al, 2004). Charrasse et al (Charrasse et al, 2006) suggest that RhoA is only upregulated after the initiation of myoblast fusion, which is not necessarily compatible with the observation that RhoA is required for upregulation of specific pro-myogenic genes (Carnac et al, 1998;Takano et al, 1998;Wei et al, 1998). Activation of RhoA, by inhibition of p190RhoGAP, enhances myogenesis and directs adipogenesis or myogenesis cell fate decisions towards the myogenic lineage (Sordella et al, 2003).…”
Section: ) (D) Northern Blot Analysis Ofmentioning
confidence: 49%
“…Myoblast interactions engage multiple receptor systems in parallel, including focalized highdensity accumulation of M-and N-cadherin, neural cell adhesion molecule (NCAM), vascular cell adhesion molecule (VCAM-1), meltrin, and integrins (Fig. 1A) (Charrasse et al 2006;Abmayr and Pavlath 2012;Ozawa 2015). Once myoblasts connect with each other, individual mobility is largely disabled, whereas collective contractility and force transmission across cell-cell junctions are gained, particularly through the actomyosin cytoskeleton, which develops prominent stress fibers under the control of RhoA and bridges multiple cell bodies for coordinated rhythmic contractility of the multicellular ensemble (Charrasse et al 2006).…”
Section: Cell-cell Adhesion States and Dynamicsmentioning
confidence: 99%
“…1A) (Charrasse et al 2006;Abmayr and Pavlath 2012;Ozawa 2015). Once myoblasts connect with each other, individual mobility is largely disabled, whereas collective contractility and force transmission across cell-cell junctions are gained, particularly through the actomyosin cytoskeleton, which develops prominent stress fibers under the control of RhoA and bridges multiple cell bodies for coordinated rhythmic contractility of the multicellular ensemble (Charrasse et al 2006). Thus, in fusing myoblasts high junction stability mediated through overlapping adhesion systems and cytoskeletal linkages support mechanically very stable junctions, which mediate collective contractility and eventually cell fusion, but discourage position change of the group as a whole and individual cells within the group.…”
Section: Cell-cell Adhesion States and Dynamicsmentioning
confidence: 99%